Reirradiation of Whole Brain for Recurrent Brain Metastases: A Case Report of Lung Cancer With 12-Year Survival - Li, Minmin; Song, Yanbo; Li, Longhao; Qin, Jian; Deng, Hongbin; Zhang, Tao (Frontiers in Oncology, 2021)
Whole brain radiotherapy (WBRT) for brain metastases (BMs) was considered to be dose limited. Reirradiation of WBRT for recurrent BM has always been challenged. Here, we report a patient with multiple BMs of non-small-cell lung cancer (NSCLC), who received two courses of WBRT at the interval of 5 years with the cumulative administration dose for whole brain as 70 Gy and a boost for the local site as 30 Gy. Furthermore, after experiencing relapse in the brain, he underwent extra gamma knife (GK) radiotherapy for local brain metastasis for the third time after 5 years. The overall survival was 12 years since he was initially diagnosed with NSCLC with multiple brain metastases. Meanwhile, each time of radiotherapy brought a good tumor response to brain metastasis. Outstandingly, during the whole survival, he had a good quality of life (QoL) with Karnofsky Performance Score (KPS) above 80. Even after the last GK was executed, he had just a mild neurocognitive defect. In conclusion, with the cautious evaluation of a patient, we suggest that reirradiation of WBRT could be a choice, and the cumulative radiation dose of the brain may be individually modified.